'He didn't want to let his team down': the challenge of dual loyalty for team physicians. Issue 3 (2nd September 2018) - Hanson, Stephen S.
ABSTRACT: Team physicians have a complicated job that involves potentially conflicting obligations to multiple entities. Though responsible for the medical care of the athletes as individuals, they also have obligations to the team that employs them which can include returning athletes to play who are at heightened risk of re-injury. The fact that the athletes and owners have some overlapping interests (e.g. players playing well and winning games) only complicates this issue. Further, there are strong financial incentives to do what is necessary to obtain and keep a position as a team physician. This article examines dual loyalty and conflict of interest in sports medicine, and argues that there is not now a widely accepted or adequate solution to either. Moving toward a solution will require fairly serious changes in the role of the team physician. Abbreviations: FIMS International Federation of Sports Medicine; NFL National Football League; MVP Most Valuable Player; RGIII Robert Griffin, III